2020
DOI: 10.31937/akuntansi.v12i2.1882
|View full text |Cite
|
Sign up to set email alerts
|

Determinan Nilai Perusahaan Publik Manufaktur Sektor Industri Barang Konsumsi 2015-2019

Abstract: This research examines several determinants that may have effect to firm value of the consumer goods manufacturing sector in Indonesia in 2015-2018, proxied with Price to Book Value (PBV). The factors that are thought to to have effect against firm value are Price Earning Ratio (PER) which shows potential future profits and investment choices, financial leverage (DER) which reflects the comparison between source of firm’s funding, Dividend Payout Ratio (DPR) which is a factor that attracts investor interest, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 1 publication
(1 reference statement)
0
4
0
Order By: Relevance
“…The high potential for dividends to be distributed will cause investors to be interested and investor demand for company shares will increase and share prices will also increase, causing an increase in the value of PBV, which will affect the increase in firm value. Hertina et al (2019), Adityaputra and Ariyanto (2020) and Dewi and Suryono (2019) found that DER has a negative effect on firm value. Contrary, Setiawan et al (2021) argued that DER has a positive influence on firm value.…”
Section: Leveragementioning
confidence: 99%
See 3 more Smart Citations
“…The high potential for dividends to be distributed will cause investors to be interested and investor demand for company shares will increase and share prices will also increase, causing an increase in the value of PBV, which will affect the increase in firm value. Hertina et al (2019), Adityaputra and Ariyanto (2020) and Dewi and Suryono (2019) found that DER has a negative effect on firm value. Contrary, Setiawan et al (2021) argued that DER has a positive influence on firm value.…”
Section: Leveragementioning
confidence: 99%
“…If the company is managed optimally, then this PBV ratio will show a value above 1 (one), which means the market value of the shares exceeds the book value. By observing PBV, management can find out how investors respond to company performance and future prospects for the company (Adityaputra and Ariyanto, 2020). This ratio is also used to measure the level of overvalued or undervalued stock prices.…”
Section: Firm Valuementioning
confidence: 99%
See 2 more Smart Citations